Pengaruh Aromaterapi Lavender dan Mawar terhadap Pengelolaan Nyeri pada Proses Persalinan - Aritonang, Tetty Rina; Rostianingsih, Dewi; Wulandari, Ayu; Antlia, Fany; Pinem, Monica Gabrilia; Samsiah, Samsiah; Khoirunisa, Sabrina; Adawiyah, Robiah (NHM PRESS, 2023)
Background: Childbirth pain is caused by visceral and somatic pain. One way to relieve childbirth pain is aromatherapy. Aromatherapy is an extract or oil obtained from plants, flowers, herbs, and trees. Objective: This Study aims to determine the effect of Lavender and Rose Aromatherapy on reducing pain in the first stage of labor. Method: This study is a review of the literature that collected Google Scholar database articles published via 2019 to 2023. Result: Based on research results by Pebi et al. 2020 there was a decrease in pain intensity in respondents before and after using lavender aromatherapy. The mechanisms of aromatherapy work through body circulation and sense of smell. The olfactory organs are directly related to the brain. There is a meaningful relationship between the mother's delivery of lavender and rose aromatherapy to the intensity of labor pains. There is a significant reduction in pain when administered with the aromatherapy of lavender and rose.